Perilaku Bermusik dalam Repertoar Rabab Pasisia Kaba Gadih Basanai - Darmansyah Darmansyah (FBS Padang State University, 2023)
Kaba Gadih Basanai is a very popular story for the Minangkabau people and gives a very deep meaning in life because there is a historical background to the life of the people in the colonial era which was full of twists and turns of heartbreaking struggles. The purpose of this study is to examine how music behaves in conveying Rabab Pasisie kaba Gadih Basanai. This research is research with a descriptive qualitative approach, the researcher makes observations, describes then gives meaning to the symbols found. The Gadih Basanai song has traditional musical elements played by all the artists all of these artists have a different musical taste for the quality of each talent they have, and different characteristics when the performers of the Rabab (Violin) arts serve it. The method used in this study is a qualitative method with a descriptive analysis approach. Musical behaviour is presented in various forms and musical variants created by each Rabab (violin) maker based on the artist's level of intelligence, to be able to give a musical sense that is presented during performances of Gadih Basanai singing or songs. Then the behaviour of the Rabab makers seems clear that the Rabab which is played through the instrument instrumental melodies often give or brings up new melodies through inspiration by the players themselves, who always synergize between instruments to become an interesting work and not out of frames the melody on the coastal Rabab itself.